Impact Assessment of Ri-Lajong FPO on the Livelihood of Farmers in Ribhoi District, Meghalaya (Indian Journal of Extension Education, 2023)
The study was carried out on Ri-Lajong Farmer Producer Organisation (FPO), Nongpoh, Ribhoi district, Meghalaya with the objective of examining the factors’ influence on the annual income of member farmers of FPO during the year 2021-22 and primary data consisted of 65 members collected from Ri-Lajong FPO. The Heckman two-stage selection model was applied. Results showed that FPO significantly influenced the income of farmers by providing various facilities to conduct activities crop production, forest products, piggeries, and fish farming. All farming activities except piggeries showed a positive response to increase the income of members of the FPO. The factors such as farmers’ education and training provided by FPO showed positive influence while hired labour had influenced negatively to the income of farmers. Therefore, the study concluded that educated youth of the state should join the FPO and attend the training program organised by the FPO as it will be helpful in income enhancement and reduce the unemployment level of the state.